Quantum Dots in Bionanotechnology and Medical Sciences: Power of the Small - Ergal, İ.; Akarsubasi, A. T. (Springer International Publishing, 2015)
Among the other bionanotechnology and nanomedicine tools Quantum Dots (QDs) have pioneered numerous advances in both fundamental and applied sciences; due to their unique optical, electronic and physical properties namely photostability, single source excitation, narrow emission, multiplexing capabilities and high quantum yield as compared to traditional fluorophore materials. New generation QDs with better biocompatibility allows studying intracellular processes in human beings at the single molecule level, to use in vitro imaging for bionanotechnological purposes, long term in vivo observation of cellular events, tumor targeting and even in diagnostics. However, further developments are necessary for robust and reproducible methods to conjugate QDs with many different biomolecules under stringent biological requirements to improve its commercial availability and further use in clinical diagnostics.